KOMUNIKASI PEMASARAN TERPADU UNTUK MENINGKATKAN JUMLAH PESERTA DIDIK DI SMA WARGA SURAKARTA - Bina Mahalalel, Adiel Brilliant (Solidaritas, 2025)
ABSTRACT The decline in the number of students at SMA Warga Surakarta is due to intense competition with other schools, especially state schools that offer free education. To overcome this challenge, the research aims to analyze the application of integrated marketing communications in increasing the number of new students at the school. The main theory used in this research is Effendi's marketing communications theory and Anang's integrated marketing communications concept, which emphasizes the use of various marketing elements such as advertising, sales promotions, public relations, direct marketing, interactive marketing, and personal selling. The research method used is descriptive qualitative with Miles and Huberman's interactive analysis approach. Data was obtained through interviews with school officials, observations, and analysis of documents related to the marketing strategies implemented. The research results show that the integrated marketing communication strategy implemented at SMA Warga Surakart is quite effective in increasing the number of students and strengthening the school's image. The use of social media, incentive-based promotional programs, as well as public relations activities such as social service and publication of student achievements have succeeded in attracting the attention of prospective students and parents. However, there are still several obstacles such as limited marketing budgets and limited student admission quotas. Therefore, schools need to optimize digital marketing strategies and increase Keywords: Marketing Communication, Integrated Marketing Communication